Revolution for our rights : indigenous struggles for land and justice in Bolivia, 1880-1952 - Gotkowitz, Laura (Durham, N.C. : Duke University Press ; Chesham : Combined Academic [distributor], 2008)
Gotkowitz provides a re-assessment of the cause of Bolivia's 1952 revolution, arguing that the revolution roots are to be found in the indigenous struggles for land and justice that swept through the country during the first half of the 20th century, as opposed to class-based movements in the 1930s, such as the mineworker unions.
Includes bibliographical references and index.
Keywords: 1900-1999; Indians of South America -- Bolivia -- Cochabamba (Dept.) -- Government relations; Indians of South America -- Civil rights -- Bolivia -- Cochabamba (Dept.); Social movements -- Bolivia -- History -- 20th century; Indians of South America -- Civil rights; Indians of South America -- Government relations; Social movements; War -- Causes; Bolivia -- History -- Revolution, 1952 -- Causes; Bolivia; Bolivia -- Cochabamba (Department); History